Challenges of the foreign policy of the Republic of Serbia in the light of the Russian-Ukrainian conflict - Stanković Nevena M. (Baština, 2023)
Exposing the unresolved political issues in the Western Balkans, the war in Ukraine has actualized the key challenges that the current Serbian foreign policy orientation is facing with. Serbia's decision not to impose sanctions on Russia due to the Russian-Ukrainian conflict has returned the focus to the issue of harmonization in the field of the Common Foreign and Security Policy, within negotiations on Serbia's membership in the EU. Considering that EU membership is a strategic priority of Serbia's current foreign policy, the author examines whether non-imposing of restrictive measures to Russia irreversibly blocks the negotiation process or represents a continuation of the same foreign policy course that highlights relations with Russia as one of the priorities. Starting from the thesis that the perspective of Serbia's membership in the EU is determined by numerous issues both within Serbia and EU, the conclusion is that Serbia's non-imposing of sanctions against Russia due to the ongoing war, does not fundamentally change the course of Serbia's accession negotiations with the EU. In terms of complex geopolitical circumstances on the one side and the absence of a defined Serbian foreign policy strategy on the other, in foreseeable future we can expect the continuation of the policy of "balancing" as a principled and pragmatic choice that advocates comparative development of relations with Brussels and Moscow.